Sale of Goods and Consumer Remedies: A Slovenian Perspective - Strojan, Lucija (Central European Academy Law Review, 2025)
Buying various goods is part of the average consumer’s daily routine. In return for the money, the consumer expects to receive goods that will serve their purpose for a reasonable period after the conclusion of the sales contract. Legal mechanisms should safeguard the principle of equivalence. The dissatisfied position of consumers in Slovenia results from older legal solutions and the implementation of new EU directives. In Slovenia, the new Consumer Protection Act entered into force in December 2022 and became applicable from January 2023. Thus, Slovenia has now fulfilled its obligations to implement Directives 2019/770 and 2019/771. Although the two Directives are complementary, this paper focuses solely on the implementation of Directive 2019/771 into the Slovenian legal order. Under the new Consumer Protection Act, the seller remains liable for any lack of conformity existing at the time of delivery of the goods which becomes apparent within two years of that time. In addition, the new law introduces new concepts (such as subjective and objective requirements for conformity) and explicitly includes goods with digital elements. Owing to the fully harmonising nature of Directive 2019/771, the new Consumer Protection Act provides for the hierarchy of remedies. Under Slovenian law, the liability of the seller is complemented by a “guarantee for proper functioning” of “technical” goods and a voluntary (commercial) guarantee option. The provision of a mandatory one-year guarantee for proper functioning has been preserved from Yugoslavia’s legal system to the present day, as the new Consumer Protection Act continues to maintain it. Thus, the Slovenian legal system continues to provide for two (legally) different but parallel mandatory frameworks for the protection of consumer interests.